Device design for contact fatigue testing of remanufactured components - Low, Steiner Tze-Zhous' (2014)
This is the report for project title A177: device design for contact fatigue testing of remanufactured components. The project centred on the fretting process of materials and the design of a specimen contact device to impart a normal force on a specimen under cyclic loading. Fretting can be classified into two major components, namely fretting wear and fretting fatigue. Fretting wear concerns about the wear properties induced by the fretting action, which includes adhesion and abrasion, while fretting fatigue studies on the nucleation of cracks on the parts in contact due to the fretting process and how fretting reduces fatigue life of the part.